Electric Phenomenon in Bones as a Result of Piezoelectricity of Hydroxyapatite - Pawlikowski, Maciej (Archives of Clinical and Biomedical Research, 2017)
Conducted biomineralogical studies indicate piezoelectric properties of apatite, which is one of the major components of bone. This publication presents hypothetical correlations between piezoelectric properties of bone apatite and the accompanying electromagnetic phenomena in bones and their environment. It notes the correlations between electrical properties of bones and changes in the electromagnetic field around bones, as well as connections between external pressure changes etc. and electrical phenomena in the bones.